2021
DOI: 10.1007/s00345-021-03666-w
|View full text |Cite
|
Sign up to set email alerts
|

BCG-unresponsive high-grade non-muscle invasive bladder cancer: what does the practicing urologist need to know?

Abstract: Purpose Bacille Calmette-Guérin (BCG) is a well-established treatment for preventing or delaying tumour recurrence following high-grade nonmuscle invasive bladder cancer (NMIBC) resection. However, many patients will experience recurrence or progression during or following BCG. This scenario has been one of the most challenging in urologic oncology for several decades since BCG implementation. Finally, significant progress has occurred lately. The aim of this review was to summarize for the practising urologis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 49 publications
0
25
0
Order By: Relevance
“…The current study ( 40 , 43 , 44 ) found that trained immunity was one of the key mechanisms of BCG immunotherapy and might provide protection against COVID-19, which may explain why “SARS-CoV-2” may be a potential research direction from Figure 7B . Furthermore, the possibility of combining BCG with other therapies, such as ICIs ( 45 , 46 ), is gaining increasing interest, and more researches are required to develop new strategies.…”
Section: Discussionmentioning
confidence: 99%
“…The current study ( 40 , 43 , 44 ) found that trained immunity was one of the key mechanisms of BCG immunotherapy and might provide protection against COVID-19, which may explain why “SARS-CoV-2” may be a potential research direction from Figure 7B . Furthermore, the possibility of combining BCG with other therapies, such as ICIs ( 45 , 46 ), is gaining increasing interest, and more researches are required to develop new strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, many patients refuse to undergo radical cystectomy or are not suitable for the procedure due to presence of comorbidities or advanced age (9). Intravesical chemotherapy is another treatment option but is less effective at preventing recurrence and progression (10).…”
Section: Introductionmentioning
confidence: 99%
“…The current first-line therapy for NMIBC (intermediate-and high-risk papillary tumors and carcinoma in situ) consists in intravesical instillations of Bacillus Calmette-Guerin (BCG) as it significantly reduces the risk of progression to muscle invasive disease as it significantly reduces the risk of progression to muscle invasive disease. However, the high recurrence rate necessitates radical cystectomy or enrollment in clinical trials (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%